Fertility after high‐dose testosterone and intracytoplasmic sperm injection in a patient with androgen insensitivity syndrome with a previously unreported androgen receptor mutation. (30th June 2013) - Tordjman, K. M.; Yaron, M.; Berkovitz, A.; Botchan, A.; Sultan, C.; Lumbroso, S.
Summary We report on a case of a man with familial, X‐linked, partial androgen insensitivity, in whom a new point mutation in the androgen receptor (AR) ligand‐binding domain (causing a valine‐to‐alanine substitution at codon 686) was identified. High‐dose prolonged testosterone therapy resulted in marked progression in patient's appearance and great improvement in sperm count and characteristics. In combination with intracytoplasmic microinjection, treatment resulted in fertility. This is believed to be the first report of such a case. This case supports high‐dose testosterone therapeutic trial in this condition. Furthermore, it underscores the possibility of achieving fertility with current endocrine and assisted reproduction modalities, making some of these X‐linked AR mutations paternally transmissible.